Gas Sensors Based on U-shaped Graphene Nanoribbons: A first-principles Study - Cuong, Nguyen Tien (VNU Journal of Science: Mathematics - Physics, 2020)
In this paper, I present first-principle calculations which are performed by using combination of DFT and NEGF methods to investigate the adsorption of CO 2 and NH 3 molecules on straight and U-shaped GNRs junctions. The density of state, molecular orbital, adsorption energy, transmission spectrum, and current-voltage characteristics were analyzed. It is found that the adsorption of CO 2 and NH 3 on straight GNRs at the dangling bond edges exhibit chemical interaction behavior with high adsorption energy. Besides, for U-shaped ZGRNs without adsorption, the states around Fermi level are quasi-bound states localized at the zigzag edges. The electrons at these localized states are almost confined and do not contribute on conductance. However, for U-shaped GRNs with CO 2 and NH 3 adsorbed on DB armchair edge defects, these states become delocalized on whole of the U-shaped junction. The current-voltage characteristics show that the sensitivity and selectivity of the U-shaped GNRs gas sensors are significantly improved in comparison with the pristine GNR ones.